In Vitro Fertilization Of Hamster Ova As An Aid In Assessing The Fertilizing Capacity Of Human Spermatozoa - Syed Mohamed, Syed zulkifli (1986)
Studies have been recently undertaken in many research laboratories to examine the fertilizing capacity of spermatozoa from human male s with histories of unexplained infer tility to investigate their ability to penetrate ova . Since human ova are not readily available , hamster ova have been used as a substitute for these studies and research is going on to test the validity o f this as say as areliable diagnostic tool for examining spermovum interaction in man and animals. A study was undertaken to develop such an as say system for evaluating the causes of 'unexplained infertility ' in males at the National Population and Family Development Board in Kuala Lumpur .